Islamic Law on Animal Rights and Welfare in the Sri Lankan Context: An Islamic Analysis on the Animal Welfare Bill of 2006 - Long, Ahmad Sunawari; Razick, Ahamed Sarjoon; Saujan, Iqbal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The almighty Allah (SWT) has created all living beings, humans, birds, animals and insects.  He is who strongly asks people to treat animals with compassion and not to abuse them which are worthy of consideration and respect. In Sri Lanka, varying concepts are followed among different communities: Buddhists and Hindus consider slaughtering quadrupeds as a cruel act. Meanwhile, Muslims consider the similar act as a divine obligation (Qurbani and Uluhiyya). This study compares the Animal Welfare Bill, initiated by the Commission of Law of Sri Lanka on 2006, with the tenets of Islamic Law (Shariah) through a review of literature and thematic content analysis to identify areas where the right of the animal is violated. According to Animal Welfare Bill of 2006, these areas refer to the slaughter of animals for meals, transport of animals, use of live animals for scientific purposes, and cruelty relating to animals. These identified areas coincide with the identified areas espoused by the Prophet Mohamed (PBUH), and a solution produced to prevent such violation with the instruction of almighty Allah around 1400 years ago.